The Swedish Language Council's Pronounciation Dictionary - The Swedish Language Council (Institute for Language and Folklore, 2024)
List containing Swedish words and their pronounication, developed by the Swedish Language Council. Each article contains an entry, pronounciation given in phonetical script alongside the part-of-speech for the word and the inflection of the word.

Lista över svenska ord och deras uttal framtagen av svenska språknämnden. Varje artikel innehåller uppslagsord, uttal i fonetisk skrift och ordets ordklass i förekommande fall även böjningsformen.
Svenska Språknämndens uttalsordbok
Keywords: Linguistics; Lingvistik; Pronounciation; Uttal; Swedish; Svenska; Dictionary; Ordbok; Phonology; Fonologi; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik